Engaging the Christian Scriptures An Introduction to the Bible - Arterbury, Andrew E.; Bellinger, W. H. Jr. 1949-; Dodson, Derek S. (Grand Rapids Baker Academic, 2021)
This one-semester textbook aids students as they engage in their first reading of the biblical text in an academic setting. Now updated and revised throughout.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books